2019
DOI: 10.1186/s13068-019-1612-7
|View full text |Cite|
|
Sign up to set email alerts
|

Common metabolic networks contribute to carbon sink strength of sorghum internodes: implications for bioenergy improvement

Abstract: BackgroundSorghum bicolor (L.) is an important bioenergy source. The stems of sweet sorghum function as carbon sinks and accumulate large amounts of sugars and lignocellulosic biomass and considerable amounts of starch, therefore providing a model of carbon allocation and accumulation for other bioenergy crops. While omics data sets for sugar accumulation have been reported in different genotypes, the common features of primary metabolism in sweet genotypes remain unclear. To obtain a cohesive and comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 126 publications
(208 reference statements)
1
5
0
Order By: Relevance
“…This result is consistent with earlier observations showing that it was the central internodes in sorghum stems that displayed the highest • Brix [27,51,59]. The sweet sorghum cultivars Della and Rio showed similarities in the internode sugar concentration dynamics, whereas in both genotypes, the total sugar concentration was remarkably increased after anthesis and the upper and lower internodes had lower sugar concentrations compared to the middle internodes [60].…”
Section: Internode Weight Rather Than Length Can Be Used As Predictor...supporting
confidence: 91%
“…This result is consistent with earlier observations showing that it was the central internodes in sorghum stems that displayed the highest • Brix [27,51,59]. The sweet sorghum cultivars Della and Rio showed similarities in the internode sugar concentration dynamics, whereas in both genotypes, the total sugar concentration was remarkably increased after anthesis and the upper and lower internodes had lower sugar concentrations compared to the middle internodes [60].…”
Section: Internode Weight Rather Than Length Can Be Used As Predictor...supporting
confidence: 91%
“…Sugarcane is one of the key biomass and bioenergy crops, providing about 80% of global sugar production and 40% of ethanol production (Zhang et al, 2018). Efforts have been made to investigate the molecular mechanisms of sugar accumulation in sugarcane and in the comparable species sweet sorghum (Li et al, 2018;Li et al, 2019a;Li et al, 2019b), from sugar transportation and physiology to transcriptome and quantitative trait loci mapping (Babu et al, 2009;Moore, 2005;Aitken et al, 2006;Casu et al, 2007;Zhang et al, 2021). Yuan et al performed transcriptomic and metabolomic studies on two sugarcane varieties and revealed candidate genes for sucrose metabolism, stem texture, and rind color.…”
Section: Applications Of Omic Approaches Provide Insights Into Biomas...mentioning
confidence: 99%
“…The original version of the article [1] unfortunately contained a mistake in author’s first name. The name of the author has been corrected from Wenqing Wang to Wenqin Wang in this correction article.…”
Section: Correction To: Biotechnol Biofuels (2019) 12:274 101186/s13mentioning
confidence: 99%
“…The name of the author has been corrected from Wenqing Wang to Wenqin Wang in this correction article. The original article [1] has been corrected.…”
Section: Correction To: Biotechnol Biofuels (2019) 12:274 101186/s13mentioning
confidence: 99%